Precarity, Health Vulnerability, and Community-Based Interventions: A Focus Group Study on the Need and Readiness for Occupational Health Posts Among Online Taxi Bike Drivers in Samarinda, Indonesia - Nur Rohmah; Rina Tri Agustini; Dina Lusiana Setyowati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Workers in informal online transport platforms face layered occupational health risks, yet remain largely outside formal protection systems. This study explores how drivers’ lived experiences of work-related symptoms and road accidents shape their perceived need for, and readiness to engage in, a community-based Occupational Health Post (OHP/Pos UKK) in Samarinda. Methods: A qualitative descriptive phenomenological approach was used to capture drivers’ everyday experiences of occupational health and safety. Forty-nine drivers were recruited through regional WhatsApp groups and participated in five Focus Group Discussions (FGDs). To assess implementation feasibility, a community meeting involving 16 stakeholders was also conducted. All data were transcribed and inductively coded using OpenCode software. Results: Four themes emerged: (1) common occupational health symptoms, (2) timing and causes of road accidents, (3) limited awareness of OHPs, and (4) conditional willingness to serve as OHP cadres. Drivers frequently reported fatigue, musculoskeletal pain, and digestive problems, with accidents occurring mostly at night when exhaustion peaked. Although knowledge of OHPs was limited, many expressed interest in regular health monitoring and community involvement, provided that roles were flexible and supported by adequate training. Stakeholders highlighted the need for legal recognition, intersectoral coordination, and structured capacity-building. Conclusion: The findings suggest that while drivers experience cumulative strain, they are open to collective prevention efforts if supported by legitimate, sustainable institutional frameworks.